Animal ethics in biology teaching and research in selected Asian countries - Robert Wallis (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Governance and regulation of the use of live animals in research and teaching is examined in Australia, Malaysia, Indonesia, the Philippines, Singapore, Thailand, China, Japan and India. A comparison of the systems in different countries will enable the determination of best practice and fit-for-purpose regulation. The most comprehensive government regulation of animal welfare in institutions covers a broad range of animals and institutions are required to have an Institutional Animal Care and Use Committee, whose membership is specified in guidelines or regulations. The work of the Committees is rigorously overseen by government and facilities that use live animals are audited externally. All countries examined have legislation governing the use of live animals in research, although only Australia and Malaysia have a fully equivalent mandated oversight of teaching. Teaching that uses live animals is partly covered in the Philippines, Japan, Singapore and Thailand This paper thus aims to review the regulation of animal use in different Asian jurisdictions in order to determine best practices that are appropriate to those settings. The most comprehensive oversight is provided in Australia and Malaysia that essentially use the same regulatory framework.